Hyperphosphorylation-Induced Tau Oligomers - Iqbal, Khalid; GONG, CHENG-XIN; Liu, Fei (Frontiers in Neurology, 2013)
In normal adult brain the microtubule associated protein tau contains 2–3 phosphates per mole of the protein and at this level of phosphorylation it is a soluble cytosolic protein. The normal brain tau interacts with tubulin and promotes its assembly into microtubules and stabilizes these fibrils. In Alzheimer disease (AD) brain tau is three to four fold hyperphosphorylated. The abnormally hyperphosphorylated tau binds to normal tau instead of the tubulin and this binding leads to the formation of tau oligomers. The tau oligomers can be sedimented at 200,000 x g whereas the normal tau under these conditions remains in the supernatant. The abnormally hyperphosphorylated tau is capable of sequestering not only normal tau but also microtubule associated protein (MAP) MAP1 and MAP2 and causing disruption of the microtubule network promoted by these proteins. Unlike ABeta and prion protein (PrP) oligomers, tau oligomerization in AD and related tauopathies is hyperphosphorylation-dependent; in vitro dephosphorylation of AD P-tau with protein phosphatase 2A (PP2A) inhibits and rehyperphosphorylation of the PP2A-AD P-tau with more than one combination of tau protein kinases promotes its oligomerization. In physiological assembly conditions the AD P-tau readily self-assembles into paired helical filaments. Missense tau mutations found in frontotemporal dementia apparently lead to tau oligomerization and neurofibrillary pathology by promoting its abnormal hyperphosphorylation. Dysregulation of the alternative splicing of tau that alters the 1 : 1 ratio of the 3-repeat : 4-repeat taus such as in Down syndrome, Pick disease and progressive supranuclear palsy leads to the abnormal hyperphosphorylation of tau.